2016
DOI: 10.3390/catal6060084
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Model for Simultaneous Adsorption/Photodegradation Process of Alizarin Red S in Water Solution by Nano-TiO2 under Visible Light

Abstract: Abstract:The simultaneous adsorption and visible light photodegradation of Alizarin Red S in water solutions were studied in real time mode by using nano-TiO 2 , such as Anatase and Aeroxide P-25, supported on polypropylene strips. Kinetic results of the overall process were compared with those obtained from separated steps of adsorption and photodegradation previously studied; kinetic advantages were evidenced with the simultaneous approach. From the study of different dye concentrations, a kinetic model has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Our previous studies regarded the preparation of Polypropylene (PP) coated with only TiO 2 , TiO 2 in combination with graphene and with gold nanoparticles and their application in the visible light photodegradation of Alizarin Red S (1,2-dihydroxy-9,10-anthraquinonesulfonic acid sodium salt or ARS) obtaining highly efficient dye degradation with an easy separation of the photocatalyst from the solution [ 29 , 30 , 31 , 32 ]. ARS is a widely used synthetic water soluble dye considered a refractory pollutant because of the difficulty in removing it through general treatments [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies regarded the preparation of Polypropylene (PP) coated with only TiO 2 , TiO 2 in combination with graphene and with gold nanoparticles and their application in the visible light photodegradation of Alizarin Red S (1,2-dihydroxy-9,10-anthraquinonesulfonic acid sodium salt or ARS) obtaining highly efficient dye degradation with an easy separation of the photocatalyst from the solution [ 29 , 30 , 31 , 32 ]. ARS is a widely used synthetic water soluble dye considered a refractory pollutant because of the difficulty in removing it through general treatments [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of illumination intensity on adsorption equilibrium coefficient of gaseous pollutant was neglected in most articles. In liquid phase photocatalysis, some authors have reported their research on the effect of the illumination intensity on both the photoreaction coefficient and the adsorption coefficient [26][27][28][29]. Du [30] found that the value of the adsorption coefficient calculated from the L-H model was illumination intensity-dependent in photodegradation of liquid dimethyl phthalate (DMP).…”
Section: Introductionmentioning
confidence: 99%
“…Dyes are generally resistant to light and moderate oxidative agents. Without proper treatment, these dyes can be stable in the water for a much longer period of time [4].…”
Section: Introductionmentioning
confidence: 99%
“…A number of physical and physicochemical technologies have been developed for the removal of dyes from aqueous solutions, including adsorption techniques [3,4], membrane processes [5,6], and degradation of dyes through oxidation under the assistant of catalysts [7][8][9][10]. Various materials have been used as adsorbents for the removal of dyes, such as biocoagulants [1], fruit peels [3], and cellulose-based bioadsorbents [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation